Factor Analysis of Operations Strategy at Umrah and Hajj Bureaus - Fien Zulfikarijah (Universitas muhammadiyah malang, 2023)
The study aims to determine the factors considered in implementing the operational strategy of Umrah and Hajj bureaus in Indonesia with 105 owners or manager respondents in New Normal conditions. The analytical tool used in this research was factor analysis with 7 variables: cost, quality, delivery, flexibility, innovation, service, technology, and differentiation with 27 variables. The results of rotation and factor reduction leave 19 variables with a total of 5 factors scilicet technology, service, quality, differentiation, and cost. This finding was interesting because literature and technology research rarely discusses technology and services that were relevant to technological developments where most services were carried out online.